An Intensive Care Outbreak Caused by Burkholderia cepacia from Bacterial Filters - Özlem Aytaç; Elif Seren Tanrıverdi; Ömür Gündağ; Feray Ferda Şenol; Gülden Eser Karlıdağ; Barış Otlu (Pathogens)
Background: We report a hospital outbreak caused by Burkholderia cepacia that occurred in 16 patients admitted to intensive care units in Elazığ, Türkiye, between 19 March and 23 April 2024. Methods: The outbreak investigation was initiated on 23 March 2024, four days after B. cepacia was detected in four different patients. Environmental samples were collected from various parts of the hospital to find the source of the outbreak. Arbitrarily Primed Polymerase Chain Reaction (AP-PCR) was performed to determine the genetic relationship between environmental and patient samples. Results: In total, 16 of 18 B. cepacia isolates were obtained from tracheal aspirate culture. A total of 10 of 16 patients developed hospital-acquired pneumonia due to B. cepacia. Among the environmental cultures in the intensive care units, only the respirator bacterial filter grew. The isolate obtained here was in the same cluster as the isolate obtained from patient samples, resulting in a dominant clustering rate of 94.4%. Conclusions: Improper and inappropriate use of respirators and equipment can lead to outbreaks. Early detection of the outbreak, identification of the source, and taking appropriate measures quickly to contain the outbreak are key.